Watermarking technique for wireless sensor networks: A state of the art - Harjito, B.; Potdar, Vidyasagar; Singh, J. (2012)
Wireless sensor networks (WSN) are used in a number of different applications including military, environment monitoring, smart spaces etc. Security is an important aspect in WSN, however given scare resources, implementing traditional cryptographic algorithms is not very well suited for WSN nodes. Hence watermarking is being investigated as an alternative security technology in WSNs because of its light resource requirements. The objective of this paper is to present a critical analysis of the existing state-of-the-art watermarking algorithms developed for WSNs. © 2012 IEEE.